IMPLEMENTASI TRANSAKSI PEMBIAYAAN GRIYA DALAM PERSPEKTIF FIKIH MU’AMALAH DI BANK SYARIAH INDONESIA KANTOR CABANG PEMBANTU SITUBONDO - Ach. Afin; R. Fakhrurrazi (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2022)
At this time there are many emerging Islamic banking with the many developments of sharia. The birth of Islamic financial institutions in Indonesia brings an interesting competitive atmosphere in the banking business discourse. In addition to the presence of conventional banks, our society is now presented with alternative options to invest their funds, of course through the presence of Islamic banking services. Islamic banking services offer products with a different scheme from conventional banks. In accordance with the title "sharia" it bears, Islamic banking claims the principle of justice in accordance with Islamic teachings as a differentiator of its identity from conventional banks. Including one of the Islamic banks in Situbondo, namely Bank Mandiri Syariah which is currently changing its name to Bank Syariah Indonesia Of all the products available at BSI, there is one financing product that is currently in great demand by the public, especially at the Bank Shariah Indonesian Cabang Situbondo Branch, namely the Griya financing product. Griya financing is short, medium, or long term financing to finance the purchase of residential (consumer) houses, both new and used, in the developer environment with a murabahah system. In relation to the murabahah concept in Fiqh Mu'amalah, it is necessary to combine its conformity with the practice of home financing transactions at BSI KCP Situbondo, where in practice the margin provisions obtained by BSI are not transparent, when purchasing property uses the practice of debt. , the delivery of money is directly given to the customer, not the BSI party who buys the needs of the customer and many other things that the author does not know. According to the author, this is not appropriate if the contract used is murabahah.